The effect of lateral confinement on gravel bed river morphology. Issue 9 (4th September 2015) - Garcia Lugo, G. A.; Bertoldi, W.; Henshaw, A. J.; Gurnell, A. M.
Abstract In this paper, we use a physical modeling approach to explore the effect of lateral confinement on gravel bed river planform style, bed morphology, and sediment transport processes. A set of 27 runs was performed in a large flume (25 m long, 2.9 m wide), with constant longitudinal slope (0.01) and uniform grain size (1 mm), changing the water discharge (1.5–2.5 L/s) and the channel width (0.15–1.5 m) to model a wide range of channel configurations, from narrow, straight, embanked channels to wide braided networks. The outcomes of each run were characterized by a detailed digital elevation model describing channel morphology, a map of dry areas and areas actively transporting sediment within the channel, and continuous monitoring of the amount of sediment transported through the flume outlet. Analysis reveals strong relationships between unit stream power and parameters describing the channel morphology. In particular, a smooth transition is observed between narrow channels with an almost rectangular cross‐section profile (with sediment transport occurring across the entire channel width) and complex braided networks where only a limited proportion (30%) of the bed is active. This transition is captured by descriptors of the bed elevation frequency distribution, e.g., standard deviation, skewness, and kurtosis. These summary statistics represent potentially useful indicators of bed morphology that are compared with other commonly used summary indicators such as the braiding index and the type and number of bars.